2017
DOI: 10.1089/dia.2016.0307
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Patterns and Associations with Glucose Control During 12-Week Randomized Free-Living Clinical Trial of Day and Night Hybrid Closed-Loop Insulin Delivery in Adults with Type 1 Diabetes

Abstract: Objectives: We evaluated patterns of meal intake, insulin bolus delivery, and fingerstick glucose measurements during hybrid closed-loop and sensor-augmented pump (SAP) therapy, including associations with glucose control.Methods: Data were retrospectively analyzed from pump-treated adults with type 1 diabetes who underwent, in random order, 12 weeks free-living closed-loop (n = 32) and 12 weeks SAP (n = 33) periods. We quantified daily patterns of main meals, snacks, prandial insulin boluses, correction bolus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…A recent study evaluating the relationship between behavioural patterns and glucose control (mean glucose, glucose variability and post‐intervention HbA 1c ) during hybrid closed‐loop use in suboptimally controlled Type 1 diabetes highlighted the impact behavioural patterns, such as eating habits, have on glucose control 13. In line with the present study, no significant association was found between bolusing frequency and mean glucose.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study evaluating the relationship between behavioural patterns and glucose control (mean glucose, glucose variability and post‐intervention HbA 1c ) during hybrid closed‐loop use in suboptimally controlled Type 1 diabetes highlighted the impact behavioural patterns, such as eating habits, have on glucose control 13. In line with the present study, no significant association was found between bolusing frequency and mean glucose.…”
Section: Discussionsupporting
confidence: 86%
“…The use of high carbohydrate, low fat diet to prevent hypoglycaemias could, however, be counterintuitive as a change from a standard diet to a low-carbohydrate diet rather has the potential to reduce the incidence of hypoglycaemias 13 , 14 . Importantly, while increased carbohydrate intake and the associated higher insulin doses give rise to larger variations in blood glucose concentrations 13 , 15 , marked reductions in glycaemic variability have been reported in studies of low-carbohydrate diets 14 , 16 . High variability of the blood glucose levels, on the other hand, is a well-known risk factor for hypoglycaemia 5 , 17 , a phenomenon that could also explain the current observations.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we consciously enrolled a broad patient population for thisstudy,including (22). The frequency of premeal bolusing also is important, emphasizing the need for ongoing diabetes education and support with the closed-loop system (23).…”
Section: Discussionmentioning
confidence: 99%